Trypanosome CNOT10 is essential for the integrity of the NOT deadenylase complex and for degradation of many mRNAs - Färber, Valentin Lutz Fabian; Erben, Esteban D.; Sharma, Sahil; Stoecklin, Georg; Clayton, Christine (Nucleic acids research, 2013)
The degradation of most eukaryotic mRNAs is initiated by removal of the poly(A) tail, and the major deadenylase activity is associated with the CCR4/CAF1/NOT complex (NOT complex). We here study the role of CNOT10, a protein that is found in human and trypanosome, but not in yeast, NOT complexes. Trypanosome (Tb) CNOT10 is essential for growth. TbCNOT10 interacted with the deadenylase TbCAF1 and the scaffold protein TbNOT1; TbCAF1 also interacted with TbNOT1 in a yeast two-hybrid assay. In both trypanosomes and human embryonic kidney cells, approximately half of CAF1 was associated with the NOT complex. Depletion of CNOT10 from human cells did not affect this association. In contrast, depletion of TbCNOT10 in trypanosomes caused a decrease in the level of TbNOT1, detachment of TbCAF1 from the complex and pronounced stabilization of most trypanosome mRNAs. Artificial tethering of TbCAF1 to a reporter mRNA in vivo resulted in mRNA degradation, and this was not affected by TbCNOT10 depletion. We conclude that in trypanosomes, TbCNOT10 may stabilize the interaction between TbCAF1 and the NOT complex. The results further suggest that TbCAF1 is only able to deadenylate mRNA in vivo if it is recruited to the mRNA through other NOT complex components.